Effect of molar concentration on the structural, optical and electrical properties of the MnS thin film prepared by spray pyrolysis. Issue 1 (March 2021) - Kadhm, Ameera J.; Atwan, Ahmed F.; Ismail, Raid A.
Abstract: In the study, manganese sulfide (MnS) thin films were deposited glass and silicon substrates at 350°C at different molar concentrations (0.05, 0.1, 0.15 and 0.2M) by using chemical spray pyrolysis technique. X-ray diffraction (XRD) studies revealed the existence of two phases of MnS namely; β-MnS and ɣ-MnS. Scanning electron microscope (SEM) showed that the films have no cracks, compact, uniform, and the grains are homogeneously distributed over the film. The optical properties studies that the optical band gap value of MnS films changed from 2.76 eV to 2.64 eV as molar concentration increased from 0.05 to 0.2M. Raman study revealed that the crystallinity of the film improved after increasing the molar concentration and the Raman peaks are belonged to2M magnon scattering. The AFM investigation exhibited that all the films show homogenous surface with and the surface roughness was a function of molar concentration. Hall effect measurement confirmed that the deposited MnS films were n-type.